Growth, Optical, Electrical and Microhardness Studies of Pure and Strontium Chloride-Doped Zinc Tris-Thiourea Sulfate (ZTS) Crystals - P. Selvarajan2*, C. Krishnan1 and (Journal of Experimental Sciences, 2010)
Single crystals of pure and strontium chloride-doped zinc tris-thiourea sulfate (ZTS) were grown from aqueous solution by the slow evaporation method. The grown crystals were transparent and colourless. The grown crystals have been subjected to single crystal X-ray diffraction to determine the unit cell dimensions. Second Harmonic Generation (SHG) for the materials was confirmed using Nd:YAG laser. The UV-visible spectra show that the grown crystals have wide optical transparency in the entire visible region. Atomic absorption study reveals the presence of strontium in the doped ZTS crystals. The density of the grown crystals was measured and it was compared with X-ray data. The DC conductivity was measured in the temperature range 30-130°C along c-direction. DC conductivity of the grown crystals increases with increase in temperature and with concentration of dopants. The micro hardness test was carried out in (100) plane and the hardness coefficient was calculated. The hardness number is found to be increasing with increase in the concentration of dopants and loads. <div style="border-right: medium none; padding-right: 0in; border-top: medium none; padding-left: 0in; padding-bottom: 1pt; border-left: medium none; padding-top: 0in; border-bottom: windowtext 1pt solid; mso-element: para-border-div; mso-border-bottom-alt: solid windowtext .5pt;"> Keywords: ZTS crystals; Doping; Single Crystal; Solution Growth; Characterization; NLO material <div style="border-right: medium none; padding-right: 0in; border-top: medium none; padding-left: 0in; padding-bottom: 1pt; border-left: medium none; padding-top: 0in; border-bottom: windowtext 1pt solid; mso-element: para-border-div; mso-border-bottom-alt: solid windowtext .5pt;"> 1Department of Physics, Arignar Anna College, Aralvoymoli-629 301, Tamil Nadu, India; 2Department of Physics, Aditanar College of Arts and Science, Tiruchendur-628 216, Tamil Nadu, India * Corresponding Author, Email: pselvarajanphy@yahoo.co.in Please Cite This Article As: C. Krishnan, P. Selvarajan. 2010. Growth, Optical, Electrical and Microhardness Studies of Pure and Strontium Chloride-Doped Zinc Tris-Thiourea Sulfate (ZTS) Crystals. J. Exp. Sci. 1(3): 23-26.